2023
DOI: 10.3390/ijerph20105866
|View full text |Cite
|
Sign up to set email alerts
|

Physical Function and Association with Cognitive Function in Patients in a Post-COVID-19 Clinic—A Cross-Sectional Study

Abstract: Patients with long-term health sequelae of COVID-19 (post-COVID-19 condition) experience both physical and cognitive manifestations. However, there is still uncertainty about the prevalence of physical impairment in these patients and whether there is a link between physical and cognitive function. The aim was to assess the prevalence of physical impairment and investigate the association with cognition in patients assessed in a post-COVID-19 clinic. In this cross-sectional study, patients referred to an outpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…This study included hospitalized and non-hospitalized post-COVID-19 participants with pre-existing respiratory disease such as asthma, and was conducted before the Omicron peak. In another study, Gunnarsson et al reported lower performance in general cognitive function in hospitalized post-COVID-19 adults compared to the non-hospitalized group, but the TMT-B was similar across the groups ( 7 ). The mean TMT-B in our study is higher than the non-hospitalized group in the study by Gunnarsson et al (154.67 (71.25) seconds vs. 88.8 (44.5)) ( 7 ) that may be explained by the lower educational level of participants in our study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study included hospitalized and non-hospitalized post-COVID-19 participants with pre-existing respiratory disease such as asthma, and was conducted before the Omicron peak. In another study, Gunnarsson et al reported lower performance in general cognitive function in hospitalized post-COVID-19 adults compared to the non-hospitalized group, but the TMT-B was similar across the groups ( 7 ). The mean TMT-B in our study is higher than the non-hospitalized group in the study by Gunnarsson et al (154.67 (71.25) seconds vs. 88.8 (44.5)) ( 7 ) that may be explained by the lower educational level of participants in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Gunnarsson et al reported lower performance in general cognitive function in hospitalized post-COVID-19 adults compared to the non-hospitalized group, but the TMT-B was similar across the groups ( 7 ). The mean TMT-B in our study is higher than the non-hospitalized group in the study by Gunnarsson et al (154.67 (71.25) seconds vs. 88.8 (44.5)) ( 7 ) that may be explained by the lower educational level of participants in our study. Also, Akinci et al showed worse performance on MoCA and TMT-A tests in young post-COVID-19 adults with mild to moderate disease 21 to 60 days following acute illness compared to healthy controls; however, there were no significant between-group differences in attention span, Stroop time, Stroop Error, and TMT-B tests ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations